2013
DOI: 10.1371/journal.pcbi.1003063
|View full text |Cite
|
Sign up to set email alerts
|

Biases in the Experimental Annotations of Protein Function and Their Effect on Our Understanding of Protein Function Space

Abstract: The ongoing functional annotation of proteins relies upon the work of curators to capture experimental findings from scientific literature and apply them to protein sequence and structure data. However, with the increasing use of high-throughput experimental assays, a small number of experimental studies dominate the functional protein annotations collected in databases. Here, we investigate just how prevalent is the “few articles - many proteins” phenomenon. We examine the experimentally validated annotation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 25 publications
2
109
0
3
Order By: Relevance
“…A function annotation method using family resources is often limited by the scope of the family resources and their ability to provide functional information only for certain aspects. Moreover, bias in protein function annotations [74] or mis-annotations affects our understanding of protein function space [11]. As a result, sometimes correct and highly specific predictions may be misinterpreted as incorrect or erroneous if they have only been experimentally annotated in a generic manner.…”
Section: Discussion / Challengesmentioning
confidence: 99%
“…A function annotation method using family resources is often limited by the scope of the family resources and their ability to provide functional information only for certain aspects. Moreover, bias in protein function annotations [74] or mis-annotations affects our understanding of protein function space [11]. As a result, sometimes correct and highly specific predictions may be misinterpreted as incorrect or erroneous if they have only been experimentally annotated in a generic manner.…”
Section: Discussion / Challengesmentioning
confidence: 99%
“…Schnoes et al [ 32 ] reported that annotations deriving from high-throughput experiments tend to consist of high-level GO terms, and tend to represent a limited number of functions. This artifi cially decreases the information content of these terms, since they are frequently annotated, and artifi cially decreased information content affects similarity analyses.…”
Section: Biases Associated With Particular Evidence Codesmentioning
confidence: 99%
“…However, at the time of writing, a small number of experimental studies contribute much of the functional protein annotations collected in the databases, thereby biasing the available experimental annotations [ 8 ]. Indeed, DNA sequencing did not achieve its dramatic cost reductions and increases in throughput fortuitously, but rather was the result of the systematic investment of hundreds of millions of dollars in technology development over two decades.…”
Section: Discussionmentioning
confidence: 99%
“…Manual curation may be thought of as more cautious, as there is typically a single protein being labeled at a time [ 8 ], whereas the goal of computational prediction is typically more ambitious: labeling a large number of proteins-possibly ignoring subtle aspects of the biological reality.…”
Section: Challenges Of Assessing Computational Prediction Of Functionmentioning
confidence: 99%